Imported malaria in Cabo Verde (2010-2024): Risks to post-elimination stability. - Adilson José DePina; Giovanni Leite Lima; António Lima Moreira; El Hadji Amadou Niang; Klauss Kleydmann S Garcia (PLOS Global Public Health)
Cabo Verde was officially certified malaria-free by the World Health Organization (WHO), following sustained public health interventions and strategic malaria elimination efforts. The country's National Strategic Plan (2020-2024) emphasized strengthening epidemiological and entomological surveillance at the archipelago's entry points (e.g., ports and airports), alongside early diagnosis and case investigation to prevent local transmission. However, imported malaria cases remain a persistent threat and challenge to prevent malaria reintroduction to maintain the elimination status. Therefore, this study aims to analyze imported malaria cases in Cabo Verde from 2010 to 2024, characterizing their locations, origins, epidemiological trends and spatial distribution. The findings aim to support evidence-based decision-making to prevent post-certification disease reintroduction. This study used an ecological time-series approach analyzing all confirmed imported malaria cases reported between 2010 and 2024 in Cabo Verde. Data was collected in collaboration with the National Malaria Control Program and the Integrated Surveillance and Response Service. Incidence, mortality, and case fatality rates were calculated. Joinpoint Regression Analysis was performed to assess time trends, and Holt-Winters additive models were applied for time-series forecasting. Spatial data visualization was also conducted. A total of 383 imported malaria cases were reported. A significant increase trend was observed from 2020 to 2024 (annual percentage change - APC): + 25.75%). Forecast models estimate approximately 80 imported cases annually in 2025 and 2026 (-23.1 to 80). Most cases were reported in Santiago Island (68.9%), particularly in Praia (80.5%). The most common sources of imported infection were Guinea-Bissau (N = 90; 23,5%), Angola (N = 73; 19.1%), Senegal (49; 15.4%, and Nigeria (29; 7.6%). Malaria reintroduction risks persist in Cabo Verde, necessitating continuous surveillance and prevention efforts. Understanding the epidemiological trends and future projections is essential for maintaining Cabo Verde's malaria-free status. Vigilance and strategic interventions, including fast and correct case identification, treatment, and follow-up of imported cases, are some actions that need to be reinforced. Accurate policies, leadership capacity, and necessary resources are key requirements for maintaining and sustaining the elimination.